Influence of plant residual compost and ash on yield and economic performance of cherry tomato (Bangladesh Journal of Scientific and Industrial Research, 2013)
A field experiment was conducted with different levels of compost, ash and their mixture to investigate the effect of compost and ash on their vegetative growth, fruiting characteristics as well as yield attributes and economic performance of cherry tomato (Solanum lycopersicum var. cerasiforme). The plots were treated with three levels of compost/ash (5. 10 and 15 t/ha) and three levels of compost+ash mixture i.e. (2.5+2.5), (5.5+5.5) and (7.5+7.5) t/ha. There were three replication for each treatment. The highest plant height, number of cluster/plant, number of flower/plant, fruit yield/plant, fruit yield/ha were obtained from the treatment T10 receiving 7.5 t compost+7.5 t ash/ha. Compost significantly increased fresh matter production of tomato fruit yield compared to the control. Between compost and ash, performance of compost was better. It was further observed that the combination of 7.5 t compost+7.5 t ash/ha appeared to be the economically viable treatment which offered maximum benefit cost ratio (3.25) for cherry tomato production. Bangladesh J. Sci. Ind. Res. 47(4), 387-392, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14067